LEGAL IMPLICATIONS OF INDONESIA'S OBLIGATIONS IN ADDRESSING ROHINGYA REFUGEES - Datu, Moh. Azwar Andi; Towadi, Mellisa (Jurnal Meta-Yuridis, 2026)
This study analyzes the legal implications of Indonesia’s failure to fulfill its obligations in addressing the Rohingya refugee crisis, viewed from both international and national legal perspectives. Although Indonesia has not ratified the 1951 Convention Relating to the Status of Refugees and its 1967 Protocol, the state nonetheless bears legal and moral responsibilities to protect refugees based on the principle of non-refoulement, recognized as a jus cogens norm universally binding on all nations. Using a normative juridical method with statutory and conceptual approaches, this research finds that Indonesia’s current refugee management—regulated under Presidential Regulation No. 125 of 2016—remains largely administrative and fails to address the substantive fulfillment of refugees’ basic rights. Such inadequacy creates legal implications at both levels: internationally, it may constitute an internationally wrongful act under the Articles on Responsibility of States for Internationally Wrongful Acts (ARSIWA) 2001; and domestically, it reveals inconsistencies between constitutional human rights principles and their implementation. Therefore, the study emphasizes the urgency of enacting a comprehensive Refugee Law to strengthen human rights protection and ensure Indonesia’s compliance with international humanitarian standards.